O que a pele anuncia: uma análise da obra de Gilka Machado para além do erotismo - Borges, Jaqueline Ferreira (2022)
This thesis aims to analyze the work of Gilka Machado (1893-1980) as the result of the process of constructing poetry and the poet, considering that there is a thematic diversity between the poems of the first book, Cristais Partidos (1915); and the last one, Velha Poesia (1965). To carry out the research, the corpus is Poesia Completa (2017), the second re-edition of the 1978 work and a book that brings together six of the ten titles published by Gilka Machado. Regarding the content of the verses, there is a duality between body and soul that moves the eroticism of the works, as well as a mobilization of the poetic persona that claims agency and voice for the black women of their time. There is a constant questioning about the place of women, which in the poems happens through the description of the senses and poetic devices such as metaphor, alliteration and assonance, building verses of artistic and political manifestation. This thesis observes freedom as an impulse for eroticism, a political act that manifests itself through the poems; also the concept of “Amefricanidade”, by GONZALEZ (2020), theorist that underlies the discussions of race, alongside CARNEIRO (2011) and FANON (2008). The concepts of DAL FARRA (2016) are substantial to think about the trajectory of the writer, as well as AGAMBEN (2007), FOUCAULT (2010) and BOURDIEU (1989), to build the hypothesis of symbolic death and the erasure imposed on the poet who appears especially in the last books, when loneliness permeates all the poems. Finally, the concepts of PAZ (1994) subsidize the discussions about form and poetry in the face of the smokescreen constructed by the critic to limit poetics to eroticism.